1982
DOI: 10.1042/bj2040831
|View full text |Cite
|
Sign up to set email alerts
|

Failure of leucine to stimulate protein synthesis in vivo

Abstract: The effect of 100 mumol of leucine on protein synthesis in several tissues was assessed in the intact rat. Leucine had no immediate effect on protein synthesis in gastrocnemius muscle, heart, jejunal serosa, jejunal mucosa or liver in rats which were fed, starved for 2 days or deprived of dietary protein for 9 days. Leucine treatment for 1 h also failed to stimulate protein synthesis in tissues of 2-day-starved animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
2

Year Published

1988
1988
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(50 citation statements)
references
References 26 publications
3
45
2
Order By: Relevance
“…These data suggest that the lower rates obtained in the study presented here result from the lack of dietary protein, and lack of enteral feeding may have contributed. This is consistent with the reduction in rates of tissue protein synthesis that occurs when young rats are starved or are given a proteinfree diet (26).…”
Section: Discussionsupporting
confidence: 70%
“…These data suggest that the lower rates obtained in the study presented here result from the lack of dietary protein, and lack of enteral feeding may have contributed. This is consistent with the reduction in rates of tissue protein synthesis that occurs when young rats are starved or are given a proteinfree diet (26).…”
Section: Discussionsupporting
confidence: 70%
“…The effects of fasting on hepatic protein synthesis in the suckling rats in our study were qualitatively similar to those reported in adult and young weaned rats (8)(9)(10). We found quantitative differences, however, depending on the stage of development.…”
Section: Methodssupporting
confidence: 75%
“…A short-term fast (24 h) in young growing and adult rats reduces the hepatic protein synthesis rate and protein mass by approximately 30 and 20%, respectively (8)(9)(10). Alternatively, in skeletal muscle, reduced protein synthesis in response to a short-term fast is greater in young rats than in older weaned rats (1 1, 12).…”
mentioning
confidence: 99%
“…This idea originally arose from experiments on muscle in vitro, but has not been con®rmed in vivo (McNurlan et al 1982;Papet et al 1992). However, leucine does behave in a peculiar way, because in many studies plasma concentration falls in response to feeding protein, which does not seem to happen to the same extent with other amino acids.…”
Section: Fasting and Feedingmentioning
confidence: 99%